Application of three-dimensional printing in plastic surgery: a bibliometric analysis - Tian, Jie; Jin, Ming-Jia; Gao, Yang (Frontiers in Surgery, 2024)
Recent years have seen the publication of numerous papers on the application of three-dimensional (3D) printing in plastic surgery. Despite this growing interest, a comprehensive bibliometric analysis of the field has yet to be conducted. To address this gap, we undertook a bibliometric study to map out the knowledge structure and identify research hotspots related to 3D printing in plastic surgery. We analyzed publications from 1995 to 2024, found in the Web of Science Core Collection (WoSCC), utilizing tools such as VOSviewer, CiteSpace, and the R package “bibliometrix”. Our analysis included 1,057 documents contributed by 5,545 authors from 1,620 organizations across 71 regions, and these were published in 400 journals. We observed a steady growth in annual publications, with Europe, Asia, North America, and Oceania leading in research output. Notably, Shanghai Jiao Tong University emerged as a primary research institution in this domain. The Journal of Craniofacial Surgery and Journal of Oral and Maxillofacial Surgery have made significant contributions to the field, with Thieringer, Florian M being the most prolific and frequently cited author. Key areas of focus include medical education and surgical procedures, with “3D printing”, “virtual surgical planning” and “reconstructive/orthognathic surgery” highlighted as future research hotspots. Our study provides a detailed bibliometric analysis, revealing the evolution and progress of 3D printing technologies in plastic surgery. As these technologies continue to advance, their impact on clinical practice and patient lives is expected to be profound.